Youth mental health in Ireland: a lot done, more to do?. (26th February 2015) - Coughlan, H.; Doyle, M.
Abstract : The emergence of a new youth mental health paradigm has challenged how we think about the provision of mental health care for adolescents and young adults. This editorial tracks the origins of this new paradigm within the field of mental health both internationally and in Ireland.